Step‐by‐step diagnosis and management of the nocebo/drucebo effect in statin‐associated muscle symptoms patients: a position paper from the International Lipid Expert Panel (ILEP). Issue 3 (10th March 2022) - Penson, Peter E.; Bruckert, Eric; Marais, David; Reiner, Željko; Pirro, Matteo; Sahebkar, Amirhossein; Bajraktari, Gani; Mirrakhimov, Erkin; Rizzo, Manfredi; Mikhailidis, Dimitri P.; Sachinidis, Alexandros; Gaita, Dan; et al.
Abstract: Statin intolerance is a clinical syndrome whereby adverse effects (AEs) associated with statin therapy [most commonly statin‐associated muscle symptoms (SAMS)] result in the discontinuation of therapy and consequently increase the risk of adverse cardiovascular outcomes. However, complete statin intolerance occurs in only a small minority of treated patients (estimated prevalence of only 3–5%). Many perceived AEs are misattributed (e.g. physical musculoskeletal injury and inflammatory myopathies), and subjective symptoms occur as a result of the fact that patients expect them to do so when taking medicines (the nocebo/drucebo effect)—what might be truth even for over 50% of all patients with muscle weakness/pain. Clear guidance is necessary to enable the optimal management of plasma in real‐world clinical practice in patients who experience subjective AEs. In this Position Paper of the International Lipid Expert Panel (ILEP), we present a step‐by‐step patient‐centred approach to the identification and management of SAMS with a particular focus on strategies to prevent and manage the nocebo/drucebo effect and to improve long‐term compliance with lipid‐lowering therapy.